Design and optimization of linearly graded-doping junction termination extension for 3.3-kV-class IGBTs - 蒋华平 陈万军 刘闯 饶祖刚 董彬 张波 (Journal of semiconductors, 2011)
A linearly graded-doping junction termination extension （LG-JTE） for 3.3-kV-class insulated gate bipo- lar transistors （IGBTs） was proposed and experimentally investigated. Unlike conventional multi-implantation uti- lizing more than one photolithography step, a single mask with injection window widths varied linearly away fi＇om the main junction to the edge was implemented in this proposed structure. Based on the simulation results, IGBTs with LG4TE structures were successfully fabricated on the domestic process platform. The fabricated devices exhibited a 3.7 kV forward-blocking voltage, which is close to the theoretical value of an ideal parallel plane case. This is the first success in fabrication 3.3-kV-class 1GBT in a domestic application.